Antimicrobials resistance pattern of escherichia coli collected from various pathological specimens - Akter, Farhana; Hossain, M. Mahboob; Rahman, Arifur; Shaha, Mukta; Amani, Amani El Abd Abu Amo (© 2012 Pakistan Journal of Biological Sciences, 2016)
This article was published in the Pakistan Journal of Biological Sciences [© 2012 Pakistan Journal of Biological Sciences] and the definite version is available at : http://dx.doi.org/10.3923/pjbs.2012.1080.1084 The Journal's website is at: http://www.scialert.net/abstract/?doi=pjbs.2012.1080.1084